2020
DOI: 10.1007/s10072-020-04576-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in adult adrenoleukodystrophy: a cross-sectional and longitudinal study

Abstract: Background Adrenoleukodystrophy (ALD) encompasses different neurological phenotypes, ranging from the most severe cerebral forms (C-ALD) to the less severe adrenomyeloneuropathy (AMN). As visual system can be varyingly involved, we aimed at exploring whether optical coherence tomography (OCT) may detect retinal abnormalities and their longitudinal changes in adult ALD patients. Methods In this cross-sectional and longitudinal study, we measured the thicknesses of peripapillary retinal nerve fiber layer (pRNFL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
2
2
1
Order By: Relevance
“…Our findings support the hypothesis that neurodegeneration of the spinal cord is reflected in the retina, and are in line with several other studies that have showed neuroretinal thinning in neurodegenerative and neuro‐inflammatory disorders, including a recent paper describing OCT in patients with ALD 11‐14 . However, similar to those studies, we cannot prove that the same pathological process (a dying‐back axonopathy) is occurring in both the spinal cord and retina.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings support the hypothesis that neurodegeneration of the spinal cord is reflected in the retina, and are in line with several other studies that have showed neuroretinal thinning in neurodegenerative and neuro‐inflammatory disorders, including a recent paper describing OCT in patients with ALD 11‐14 . However, similar to those studies, we cannot prove that the same pathological process (a dying‐back axonopathy) is occurring in both the spinal cord and retina.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings support the hypothesis that neurodegeneration of the spinal cord is reflected in the retina, and are in line with several other studies that have showed neuroretinal thinning in neurodegenerative and neuro-inflammatory disorders, including a recent paper describing OCT in patients with ALD. [11][12][13][14] However, similar to those studies, we cannot prove that the same pathological process (a dying-back axonopathy) is occurring in both the spinal cord and retina. Although it seems unlikely that there is a second, unrelated cause for the retinal neurodegeneration in patients with ALD, only a pathological study in which both spinal cord and retinal nerve fibers are examined could definitively resolve this issue.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…However, the visual system may be involved and neurodegeneration of the spinal cord in ALD has been correlated with pRNFL thickness 78 . In a cross-sectional and longitudinal study on 11 symptomatic adult ALD males, Bianchi-Marzoli et al 79 showed that OCT can reveal retinal abnormalities in the most disabled patients, particularly in the inferior pRNFL and inner macula.…”
Section: Optical Coherence Tomography In Other Neurodegenerative Dise...mentioning
confidence: 99%